1988
DOI: 10.1136/bmj.297.6655.1024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serum luteinising hormone concentrations on ovulation, conception, and early pregnancy loss in polycystic ovary syndrome.

Abstract: repaired or not, does not preclude patients from holding an ordinary driving licence." Possibly this statement should be extended to include suggestions relating to screening of patients of the relevant age group and sex to identify such high risk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(130 citation statements)
references
References 14 publications
4
120
0
6
Order By: Relevance
“…However, as endocrine disturbances such as insulin resistance and elevated LH levels appear, the quality of the oocytes is affected. This has been shown previously concerning high tonic LH levels in PCOS women (24) and is further reinforced by the present study, in which a relationship between insulin resistance and poor oocyte quality is demonstrated.…”
Section: Discussionsupporting
confidence: 90%
“…However, as endocrine disturbances such as insulin resistance and elevated LH levels appear, the quality of the oocytes is affected. This has been shown previously concerning high tonic LH levels in PCOS women (24) and is further reinforced by the present study, in which a relationship between insulin resistance and poor oocyte quality is demonstrated.…”
Section: Discussionsupporting
confidence: 90%
“…Kolbianakis et al have suggested that high concentrations of LH or exposure to high levels of LH and E2 in the early follicular phase may exert detrimental effects on the success of ovulation induction and conception, thus functioning as a causal factor in early pregnancy loss (21)(22)(23)(24). This is feasible either by introducing antagonist administration earlier in the cycle or pretreating patients with the oral contraceptive pill, thus suppressing gonadotropins at the start of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that high concentrations of LH during the follicular phase of stimulation can have a negative impact on oocyte quality, pregnancy rate and incidence of miscarriage (Stanger and Yovich, 1985; Howies © European Society for Human Reproduction and Embryology et al, 1986;Homburg et al, 1988;Regan et al, 1990;Shoham et al, 1990). Several centres therefore substituted HMG partially or completely by pure FSH (Venturoli et al, 1986;Diedrich et al, 1987).…”
Section: Introductionmentioning
confidence: 99%